2020
DOI: 10.1109/tnnls.2019.2956015
|View full text |Cite
|
Sign up to set email alerts
|

Robust Triple-Matrix-Recovery-Based Auto-Weighted Label Propagation for Classification

Abstract: The graph-based semi-supervised label propagation algorithm has delivered impressive classification results. However, the estimated soft labels typically contain mixed signs and noise, which cause inaccurate predictions due to the lack of suitable constraints. Moreover, available methods typically calculate the weights and estimate the labels in the original input space, which typically contains noise and corruption. Thus, the encoded similarities and manifold smoothness may be inaccurate for label estimation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In addition, ODMTCNet achieves better performance than that of state-of-the-art algorithms. Furthermore, it is observed that ODMTCNet obtains higher recognition accuracy than the algorithms in [40,41,42] even with less training samples, validating its effectiveness on image feature representation. Again, the number of filters L i (i=1, 2) associated with the optimal performance is 8 (e.g., L 1 = L 2 = 8) as given in TABLE 5, less than the number of classes 80.…”
Section: The Eth-80 Databasementioning
confidence: 77%
“…In addition, ODMTCNet achieves better performance than that of state-of-the-art algorithms. Furthermore, it is observed that ODMTCNet obtains higher recognition accuracy than the algorithms in [40,41,42] even with less training samples, validating its effectiveness on image feature representation. Again, the number of filters L i (i=1, 2) associated with the optimal performance is 8 (e.g., L 1 = L 2 = 8) as given in TABLE 5, less than the number of classes 80.…”
Section: The Eth-80 Databasementioning
confidence: 77%
“…In [54], a novel adaptive transductive label propagation approach was proposed by joint discriminative clustering on manifolds for representing and classifying high-dimensional data. In [55], to acquire a more accurate prediction in classification, the triple matrix recovery-based robust auto-weighted label propagation framework (ALP-TMR) was proposed by introducing a TMR mechanism to remove noise or mixed signs from the estimated soft labels and improve the robustness to noise and outliers in the steps of assigning weights and predicting the labels simultaneously.…”
Section: B Transductive Methodsmentioning
confidence: 99%
“…Next, we will verify the label propagation ability of the GLLP method through experiments, and make the results more intuitively observed by everyone through the visualization method. In order to fully prove the superior performance of the proposed GLLP method, five latest graph-based label propagation algorithms are selected as baselines for comparison: ALP [27] (autoweighted label propagation):, BPFLP [28](belief-peaks clustering based on fuzzy label propagation), GLP [29](graph layout based label propagation), LNLP [30](linear neighborhood label propagation) and NLPPC [31] of our proposed GLLP method is the highest. In the process of label propagation, ALP and BPFLP propagates negative labels to positive labels, which is over propagation.…”
Section: B Verification Of Label Propagation Performancementioning
confidence: 99%